Using CorMatrix for partial and complete (re)construction of arteriovenous fistulas in haemodialysis patients: (Re)construction of arteriovenous fistulas with CorMatrix. Issue 6 (November 2019) - Leskovar, Bostjan; Furlan, Tjasa; Poznic, Simona; Hrastelj, Miran; Adamlje, Anton
Introduction: CorMatrix is an acellular extracellular matrix that acts as a biological scaffold and remodels into site-specific tissue. We used it for the (re)construction of arteriovenous fistulas. Methods: In this prospective pilot case study, we used CorMatrix in six patients. We included patients who required vascular access reconstruction due to thrombosis of unsalvageable arteriovenous fistulas, patients with high-flow arteriovenous fistulas and patients with microvasculature in which autologous arteriovenous fistulas did not mature, requiring reconstruction with a graft. We sutured the CorMatrix plate into a tubular shape and then constructed arterial and venous anastomoses. Results: There were no periprocedural complications, CorMatrix-related infections, bleeding or limb swelling after the procedures. CorMatrix was first punctured after 8–10 weeks. In five patients, a percutaneous angioplasty due to CorMatrix stenosis was performed; in one patient, a stent was placed due to refractory stenosis. We observed eight thromboses during the observation period (four in one patient). Perianastomotic stenosis of CorMatrix and interdialytic hypotension were the causes of the thrombosis in five patients, cephalic arch stenosis in two patients and thromboembolism to the brachial artery and arteriovenous fistula in one patient. Thrombendarteriectomy was successful in 87.5% of patients, and one patient required arteriovenous fistula reconstruction. After a median observation period of 12.5 (range 4–23) months, all arteriovenous fistulas were patent, with a median brachial artery flow of 1450 (range 700–1700) mL/min. Conclusion: Arteriovenous fistula (re)construction with CorMatrix seems to be feasible and safe, with a relatively high incidence of neointimal hyperplasia, predominantly at venous anastomoses, but additional clinical studies are needed.